Defect‐Free, Highly Uniform Washable Transparent Electrodes Induced by Selective Light Irradiation. Issue 21 (17th April 2018) - Zhong, Zhaoyang; Woo, Kyoohee; Kim, Inhyuk; Kim, Hyuntae; Ko, Pyeongsam; Kang, Dongwoo; Kwon, Sin; Kim, Hyunchang; Youn, Hongseok; Moon, Jooho
Abstract: A simple route to fabricate defect‐free Ag‐nanoparticle–carbon‐nanotube composite‐based high‐resolution mesh flexible transparent conducting electrodes (FTCEs) is explored. In the selective photonic sintering‐based patterning process, a highly soft rubber or thin plastic substrate is utilized to achieve close and uniform contact between the composite layer and photomask, with which uniform light irradiation can be obtained with diminished light diffraction. This well‐controlled process results in developing a fine and uniform mesh pattern (≈12 μm). The mesh patternability is confirmed to be dependent on heat distribution in the selectively light‐irradiated film and the pattern design for FTCE could be adopted for more precise patterns with desired performance. Moreover, using a very thin substrate could allow the mesh to be positioned closer to the strain‐free neutral mechanical plane. Due to strong interfacial adhesion between the mesh pattern and substrate, the mesh FTCE could tolerate severe mechanical deformation without performance degradation. It is demonstrated that a transparent heater with fine mesh patterns on thin substrate can maintain stability after 100 repeated washing test cycles in which a variety of stress situations occurring in combination. The presented highly durable FTCE and simple fabrication processes may be widely adoptable for various flexible, large‐area, and wearable optoelectronic devices. Abstract : Extremely flexible transparent conducting electrodes with silver nanoparticle–carbon nanotube‐based well‐defined and uniform mesh can be successfully fabricated by a photonic sintering‐derived simple patterning route, showing exceptional durability after 100 washing test cycles, in which a variety of stress situations such as rubbing, folding, and crumpling occurs in combination.